Redes curatoriais: procedimentos comunicacionais no sistema da arte contemporânea - Carvalho, Ananda (2014)
This research seeks to map the creation procedures of curatorial networks, understanding them as communication practices in contemporary art system. Such networks are mappings of these procedures, developed by curators in contemporary art exhibitions, mainly in São Paulo city in the last decade. From the methodological point of view, the research analyzes the objects according to the theory of the creation processes in network proposed by Cecilia Almeida Salles. From the communication point of view, it likewise relies on the theory of complex thinking developed by Edgar Morin. To understand the term contemporary art, this research agrees with Anne Cauquelin, who argues for the existence of an art system that prevails in a communication society. The thesis begins by presenting the introductory courses of curatorial networks with the aim of demonstrating their complexity. Then, it observes the São Paulo s curatorial production from files used for the communication of the exhibitions as curatorial texts, interviews with curators published in the press, photographs and videos of the exhibitions. Through the analysis of these files, the research highlights three major procedures: the relationship between curating and reconstruction of historical discourse; the spatialization of curatorial thinking through exhibition s resources as texts and the organization of the artworks in the space; and the relationship between curating and distribution, that accounts discourse practices that trespass one another, connecting the production and the reception processes. It also analyzes curatorships with historic importance those contextualize the mapped procedures. The three major procedures are broken down into several others, that could interact with each other forming communicative spaces from the perspective of a complex system. Finally, this thesis presents a broad overview of the studied field with a methodological approach that provides the curatorship analysis under an unprecedented point of view of the subject in Brazil